Enfance et détention correctionnelle. Le cas du tribunal des jeunes de Winnipeg entre 1930 et 1959 - Théorêt, Bruno (Criminologie, 1995)
In 1908, the first Canadian juvenile court was established in Winnipeg. The study of the functioning of this court during the period 1930-1959 shows that the judicial process and the sentencing decisions were in relation with two different approaches to delinquency. The first approach is the criminal one. Conceptually, this approach is close to the justice model, borrowed from adult courts which operate with retribution and deterrence. The second approach is the socio-penal approach. This approach is linked to the legal (and social) status of children characterized by the obligations of acceptable adult supervision, fixed place of residence, restrained presence in public places and sexual moralization. It includes types of delinquencies for which adults cannot be incriminated and delinquencies related to contacts with the Court. The sentencing of girls and boys whose files correspond to the criminal model is characterized by the recourse to fining, reprimand, probation and restitution while those whose files match the socio-penal model are punished by correctional detention, probation, release and fine.